2019
DOI: 10.1186/s13148-019-0627-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of recurrent venous thromboembolism and circulating microRNAs

Abstract: Background Patients with unprovoked first venous thromboembolism (VTE) are at a high risk of recurrence. Although circulating microRNAs (miRNAs) have been found to be associated with VTE and are markers of hypercoagulability, this study is the first to examine whether circulating miRNAs are associated with the risk of VTE recurrence. Results A nested case-control study design was used where plasma samples were obtained from 78 patients with unprovoked VTE from the Malmö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 72 publications
3
40
0
Order By: Relevance
“…Three years later, Sun et al (2020) [52] demonstrated that over-expression of miR-103a-3p by viral construct resulted in decreased venous thrombus formation in experimental DVT. Such finding reinforces the potential role of miR-103a-3p in the pathogenesis of VTE, since this miRNA has also been found to be downregulated in VTE patients in three different studies [52,54,55] as previously described (Table 2). Zhang et al (2020) [53] reported that intravenous administration of miR-338-5p mimics resulted in decreased interleukin-6 expression and venous thrombus formation.…”
Section: Modulation Of Mirna Activity In Animal Models Of Venous Throsupporting
confidence: 89%
See 2 more Smart Citations
“…Three years later, Sun et al (2020) [52] demonstrated that over-expression of miR-103a-3p by viral construct resulted in decreased venous thrombus formation in experimental DVT. Such finding reinforces the potential role of miR-103a-3p in the pathogenesis of VTE, since this miRNA has also been found to be downregulated in VTE patients in three different studies [52,54,55] as previously described (Table 2). Zhang et al (2020) [53] reported that intravenous administration of miR-338-5p mimics resulted in decreased interleukin-6 expression and venous thrombus formation.…”
Section: Modulation Of Mirna Activity In Animal Models Of Venous Throsupporting
confidence: 89%
“…It is noteworthy that among all miRNAs characterized in the fourteen studies described in Table 2, only six miRNAs were identified in more than one study. In the context of VTE, miR-532 [44,55], miR-320a [51,54], miR-320b [51,54], and miR-424-5p [45,54] were found to be upregulated, miR-103a-3p [52,54,55] was downregulated, and miR-27b yielded conflicting results, as it was up-and downregulated [50,55]. Several factors may account for the poor reproducibility among studies such as differences in clinical characteristics of participants, time from the occurrence of the thrombotic event to blood sampling, conditions of sample collection, sample processing (e.g., centrifugation speed and time) and storage, protocol used for RNA isolation, and methods for miRNA quantification and data normalization [20,58].…”
Section: Methodological Challenges and Future Perspectives In Epidemimentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research studies have highlighted the important role of miRNAs in hemostasis and thrombosis [16][17][18][19]. Our previous studies have also demonstrated the dysregulation of some miRNAs in blood samples of HA patients compared to healthy controls and their direct interaction with human F8-mRNA [4,5].…”
Section: Discussionmentioning
confidence: 74%
“…16 Unbiased "omics" approaches that measure circulating microRNAs has identified candidates that are associated with VTE recurrence. 17 Metabolic screening has also shown potential to identify new biomarkers that influence VTE. 18,19 In sum, personalized approaches to treatment that integrate thrombus pathophysiology, circulating biomarkers, patient characteristics, and patient preferences require study.…”
Section: T1 -Translational Research: From Animals To Humansmentioning
confidence: 99%